Prognostic and diagnostic value of eosinopenia, C-reactive protein, procalcitonin, and circulating cell-free DNA in critically ill patients admitted with suspicion of sepsis - Garnacho-Montero, Jose (Crit Care, 2014)
INTRODUCTION: The aims of this study were to assess the reliability of circulating cell-free DNA (cf-DNA) concentrations, compared with C-reactive protein (CRP), procalcitonin (PCT) and eosinophil count, in the diagnosis of infections in patients with systemic inflammatory response syndrome (SIRS) and their prognostic values in a cohort of critically ill patients. METHODS: We conducted a prospective cohort study in a medical-surgical intensive care unit of a university hospital. Eosinophil count and concentrations of cf-DNA, CRP, and PCT were measured in patients who fulfilled SIRS criteria at admission to the intensive care unit (ICU) and a second determination 24 hours later. DNA levels were determined by a PCR method using primers for the human beta-haemoglobin gene. RESULTS: One hundred and sixty consecutive patients were included: 43 SIRS without sepsis and 117 with sepsis. Levels of CRP and PCT, but not cf-DNA or eosinophil count, were significantly higher in patients with sepsis than in SIRS-no sepsis group on days 1 and 2. PCT on day 1 achieves the best area under the curve (AUC) for sepsis diagnosis (0.87; 95% confidence interval = 0.81-0.94). Levels of cf-DNA do not predict outcome and the accuracy of these biomarkers for mortality prediction was lower than that shown by APACHE II score. PCT decreases significantly from day 1 to day 2 in survivors in the entire cohort and in patients with sepsis without significant changes in the other biomarkers. CONCLUSIONS: Our data do not support the clinical utility of cf-DNA measurement in critical care patients with SIRS. PCT is of value especially for infection identification in patients with SIRS at admission to the ICU.